Special Transfer Section for Selective Rejecting and Amplification of Bands in Equalization - Roman Šotner; Marek Svoboda; Dmitrii Semenov; Ladislav Polák; Jan Jeřábek; Radek Theumer; Winai Jaikla (IEEE Transactions on Circuits and Systems I Regular Papers, 2024)
This paper introduces a novel and simple filtering topology for band-reject (notch) and inverse band-reject applications, utilizing two voltage-adjustable operational transconductance amplifiers. The utilization of these active devices enables the implementation of identical topologies for both band-reject and inverse band-reject transfer functions. The resulting responses are harnessed for the cascade synthesis of a specialized comb filter, capable of amplification or attenuating/rejecting specific bands shown on three sub-bands. Both the design of individual sections and the entire cascade have been experimentally verified using active devices manufactured in the TSMC 180 nm CMOS process. Measurements conducted over a range from 10 Hz to 100 kHz demonstrate the importance of the selective filtering, which is significant for various applications, particularly in acoustic, vibration, and magnetic sensing readouts. The example of peaking suppression in magnitude response of emulated environment (acoustic coupling of piezo and microphone) is shown.
Keywords: Wireless Power Transfer Systems; Electromagnetic Compatibility and Noise Suppression; Energy Harvesting in Wireless Networks